A Cross-Sectional Study Comparing Two Opt-Out HIV Testing Strategies in the Out-Patient Setting - Tam, Greta; Wong, Samuel Yeung Shan (Frontiers in Public Health, 2021)
Background: HIV infections are generally asymptomatic, leading to undetected infections and late-stage diagnoses. Although routine opt-out HIV screening is recommended for adults in all healthcare settings, there are a lack of acceptable testing strategies. Methods: A cross-sectional study was conducted in a primary care clinic over a four-week period in 2016 to 2017 and in a specialist out-patient clinic over a concurrent 11-month period. Patients were invited to complete a questionnaire assessing demographic characteristics, acceptance of opt-out HIV testing as a policy in all out-patient clinics in Hong Kong and reasons if refusing the HIV test. All respondents were offered an HIV test. Results: This study included 648 and 1603 patients in the primary care and specialist out-patient clinic respectively. Test acceptability was 86% and 87% in the primary care and specialist out-patient setting respectively. Test uptake was 35% and 68% in the primary care and specialist out-patient setting respectively. No HIV infections were detected. Conclusion: Opt-out HIV testing during routine blood taking in the specialist out-patient setting achieved a high test uptake and acceptability. In contrast, opt-out HIV testing using rapid finger-prick tests in the primary care setting was not effective.